Activation of small conductance calcium-activated potassium channels suppresses seizure susceptibility in the genetically epilepsy-prone rats. (February 2020) - Khandai, Padmini; Forcelli, Patrick A.; N'Gouemo, Prosper
Abstract: Small conductance calcium-activated potassium (SK) channels dampen neuronal excitability by contributing to slow afterhyperpolarization (AHP) that follows a series of action potentials, and therefore may represent an intrinsic inhibitory mechanism to prevent seizures. We have previously reported that susceptibility to acoustically evoked seizures was associated with downregulation of SK1 and SK3 subtypes of SK channels in the inferior colliculus of the moderated seizure severity strain of the genetically epilepsy-prone rats (GEPR-3s). Here, we evaluated the effects of 1-ethyl-2-benzimidazolinone (1-EBIO), a potent activator of SK channels, on acoustically evoked seizures in both male and female adult GEPR-3s at various time points post-treatment. Systemic administration of 1-EBIO at various tested doses suppressed seizure susceptibility in both male and female GEPR-3s; however, the complete seizure suppression was only observed following administration of relatively higher doses of 1-EBIO in females. These findings indicate that activation of SK channels results in anticonvulsive action against generalized tonic-clonic seizures in both male and female GEPR-3s, with males exhibiting higher sensitivity than females. Highlights: Normal: the NCX forward mode transports Ca 2+ out and Na + into the neuron. PTZ-induced seizures: the NCX reverse mode transports Na + out and Ca 2+ into the neuron. NCX inhibitors reduced the incidence and severity of seizures. NCX inhibitors potentiate the sub-effective dose of diazepam in suppressing seizures.